Six new species in the genus Innobindus Jacobi 1928 (Hemiptera: Auchenorrhyncha: Fulgoromorpha: Cixiidae: Brixiini) - Löcker, Birgit (European Journal of Taxonomy, 2023)
Six new species are described in the Australian planthopper genus Innobindus Jacobi, 1928. A new species group, the artus group, is created for Innobindus artus sp. nov., I. kaanti sp. nov. and I. loriensis sp. nov.; Innobindus gimani sp. nov. is added to the licinus group and I. geminatus sp. nov. to the multimaculatus group. Another new species, Innobindus oppositus sp. nov., could not be assigned to a species group as it shows unique features within Innobindus regarding forewing venation and chaetotaxy. A checklist and identification key to males of all 13 species of Innobindus is provided. Innobindus is endemic to the eastern parts of New South Wales and Queensland, distribution maps for each species are presented